Blocking α2δ-1 Subunit Reduces Bladder Hypersensitivity and Inflammation in a Cystitis Mouse Model by Decreasing NF-kB Pathway Activation - Boudieu, Ludivine; Mountadem, Sarah; Lashermes, Amandine; Meleine, Mathieu; Ulmann, Lauriane; Rassendren, François; Aissouni, Youssef; Sion, Benoit; Carvalho, Frédéric Antonio; Ardid, Denis (Frontiers in Pharmacology, 2019)
Bladder pain is frequently associated with bladder inflammation, as in conditions like interstitial cystitis (IC), for which current analgesic therapies have limited efficacy. The antinociceptive effect of alpha-2-delta (α2δ) ligands on inflammation-associated visceral pain like that experienced in cystitis has been poorly investigated. To investigate the effect of pregabalin (PGB), an α2δ ligand, we evaluated its impact on mechanical hyperalgesia in a mouse model of cystitis induced by cyclophosphamide (CYP). We further studied its effect on inflammation and NF-B pathway activation. Acute cystitis was induced by intraperitoneal injection of 150mg.kg-1 of CYP in C57Bl/6J male mice. Pregabalin was subcutaneously injected (30mg.kg-1) three hours after CYP injection. The effect of PGB on CYP-induced mechanical referred hyperalgesia (abdominal Von Frey test), inflammation (organ weight, cytokine production, α2δ subunit level, NF-B pathway activation) were assessed one hour after its injection. In parallel, its effect on cytokine production, α2δ subunit level and NF-B pathway activation was assessed in vitro on peritoneal exudate cells stimulated with LPS. Pregabalin treatment decreased mechanical referred hyperalgesia. Interestingly, it had an anti-inflammatory effect in the cystitis model by reducing pro-inflammatory cytokine production. Pregabalin also inhibited NF-B pathway activation in the cystitis model and in macrophages stimulated with LPS, in which it blocked the increase in intracellular calcium. This study shows the efficacy of PGB in hypersensitivity and inflammation associated with cystitis. It is therefore of great interest in assessing the benefit of α2δ ligands in patients suffering from cystitis.